Ludo-Based Learning Media for Integer Addition Mastery in Elementary Students: Media Pembelajaran Berbasis Ludo untuk Penguasaan Penjumlahan Bilangan Bulat pada Siswa Sekolah Dasar - Diana, Dwi Alvinah Nur; Wardana, Mahardika Darmawan Kusuma (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Learning media play an essential role in improving students’ mathematical understanding, especially in elementary education where difficulties in integer operations are common. Specific Background: Students at SDN Kupang still struggle with integer addition due to limited use of interactive media. Gap: Previous studies highlight the benefits of educational games, yet few develop structured, validated media tailored to integer addition. Aim: This study aims to develop a Ludo-based learning media for integer addition that is valid, practical, and effective. Results: Expert validation showed an average score of 3.46 (very good), student practicality reached 3.3 (very good), and effectiveness achieved an N-Gain of 0.58 (medium), indicating improved learning outcomes. Novelty: This study introduces “Luriung,” a modified Ludo game specifically designed to support integer addition learning. Implications: The media can serve as an alternative tool for mathematics learning, encouraging active engagement and supporting conceptual understanding. Highlights:• Media improves student engagement• Valid and practical learning tool• Supports integer addition mastery Keywords: Ludo, Learning Media, Integer Addition, Elementary Mathematics, ADDIE Model